Review: Vincanne Adams (ed.), Metrics. What Counts in Global Health (2016)
Metrics: What Counts in Global Health is a compilation of works edited by Vincanne Adams about the impact of metrics in the shaping of Global Health. The book provides a set of ethnographies about the ways in which numbers and measurement are practiced in Global Health from the estimation of maternal mortality rates in Malawi to the tensions of integrating ethnography to RCT in the Veteran Administration in the U.S. These different stories show how healthcare has been transformed by new forms of governing Global Health based on the actuarial calculation of life as returns to donors’ investments. The authors warn about the consequences of this regimen in which data production overshadows actual healthcare provision. The book offers a strong statement about the importance of ethnography and qualitative accounts of the complexities and contradictions of Global Health.